2018
DOI: 10.3390/ijerph15112382
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life in People with Rare Hereditary Connective Tissue Disorders: Marfan Syndrome

Abstract: Background: The aim of this study was to analyze data on oral health-related quality of life (OHRQoL) in people with Marfan syndrome and to obtain information on the diagnosis period, orthodontic treatment, and oral symptoms. Methods: A questionnaire was developed consisting of open questions and the standardized German version of the OHIP-14 (Oral Health Impact Profile) questionnaire for the evaluation of OHRQoL. The age of diagnosis, time period from the first signs of the disease to diagnosis, and OHIP-valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Of note, most of the unaffected family members included in this study were adult females (81.3%), which may be seen as a limitation for the comparison with the affected group. However, based on the literature, OHIP-14 has been extensively reported to be gender-neutral for both the general population [4] and patients with other rare connective tissue disorders [811]. Moreover, as shown above, both gender and age were found to have no significant effect on OHIP-14 scores in the cohort of patients with LDS.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Of note, most of the unaffected family members included in this study were adult females (81.3%), which may be seen as a limitation for the comparison with the affected group. However, based on the literature, OHIP-14 has been extensively reported to be gender-neutral for both the general population [4] and patients with other rare connective tissue disorders [811]. Moreover, as shown above, both gender and age were found to have no significant effect on OHIP-14 scores in the cohort of patients with LDS.…”
Section: Resultsmentioning
confidence: 92%
“…Rare diseases have a negative impact on general health-related quality of life for patients [21]. Several studies suggest that rare diseases can also have an undesirable impact on the oral health-related quality of life due to associated abnormal dental and craniofacial findings [811, 2224]. Our study demonstrates for the first time that patients with LDS have worse OHRQoL when compared to both unaffected family members and the general U.S. population [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design used in this study has already been described in previous works [15,16,17]. The study was designed as a cross-sectional questionnaire cohort study in people with ectodermal dysplasia to evaluate their respective OHRQoL.…”
Section: Methodsmentioning
confidence: 99%
“…Our research group showed previously that the oral health-related quality of life (OHRQoL) is affected by rare diseases presenting oral manifestations [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%